Serotonin - A Chemical Messenger Between All Types of Living Cells 2017
DOI: 10.5772/intechopen.69165
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function of Serotonin in Bivalve Molluscs

Abstract: It has been observed that 5-HT excites the heart nerves in hard clam and regulates contraction and relaxation of the anterior byssus retractor muscle in the blue mussel. It is now known that 5-HT regulates several neurobehavioral systems such as mood, appetite, sleep, learning, and memory. It also plays critical roles in the physiological functions of peripheral organs involved in stress, growth, and reproduction in the animal kingdom. The present study reviews conserved 5-HT biosynthesis and its localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 118 publications
(152 reference statements)
1
11
0
Order By: Relevance
“…Actually, we found that approximately 56% of the cells in the CPGs of Cr. grayanus are 5-HT-LIP neurons (the "serotonic center" of the visceral nervous system consisting of the CPG, VG and their nerve connections), in agreement with previous observations that in the clams Tresus capax and Macoma nasuta (Smith, 1982;Alavi et al, 2017) the level of 5-HT is higher in the CPG than the VG. The 5-HT content of bivalve ganglia is influenced by the reproductive cycle, seasonal physiological activities, and various stress factors (Fingerman and Nagabhushanam, 1997).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Actually, we found that approximately 56% of the cells in the CPGs of Cr. grayanus are 5-HT-LIP neurons (the "serotonic center" of the visceral nervous system consisting of the CPG, VG and their nerve connections), in agreement with previous observations that in the clams Tresus capax and Macoma nasuta (Smith, 1982;Alavi et al, 2017) the level of 5-HT is higher in the CPG than the VG. The 5-HT content of bivalve ganglia is influenced by the reproductive cycle, seasonal physiological activities, and various stress factors (Fingerman and Nagabhushanam, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…grayanus, in 49.8% of the total number of neurons in the visceral ganglia up to 87% in the cerebropleural ganglia. Moreover, the nervous system of bivalves contains much higher 5-HT concentrations than that of other invertebrates (Alavi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This module was enriched for tryptophan metabolic processes and included the tryptophan 2,3-dioxygenase coding gene (TDO), a pivotal regulator of systemic tryptophan levels also involved in the response to oxidative stress ( 67 , 68 ). Tryptophan is the precursor of 5-hydroxytryptamine (5-HT), a bivalve serotonin transmitter that plays critical roles in numerous physiological functions (e.g., reproduction ( 69 )). In the coral Montastrea faveolata (now known as Orbicella faveolata ), TDO (called AGAP in the reference [94]) was up-regulated in response to ultraviolet radiation in larvae and was associated with individual fitness (locomotion and settlement) impairment in later stages ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is the precursor of 5-hydroxytryptamine (5-HT), a bivalve serotonin transmitter that plays critical roles in numerous physiological functions (e.g., reproduction; Alavi, Nagasawa, Takahashi, & Osada, 2017). In larvae from the coral Orbicella faveolata, TDO (referred to as AGAP) was upregulated in response to ultraviolet radiation, and larval fitness (locomotion and settlement) went on to suffer (Aranda et al, 2011).…”
Section: Effect Of Prolonged Exposure To Elevated Temperature On Thmentioning
confidence: 99%